Modulating Effects of Contextual Emotions on the Neural Plasticity Induced by Word Learning - Guo, Jingjing; Li, Dingding; Bi, Yanling; Chen, Chunhui (Frontiers in Human Neuroscience, 2018)
Numerous studies have investigated the neuro-cognitive mechanism of learning words in isolation or in semantic contexts recently. However, emotion as an important influencing factor on novel word learning has not been fully considered in the previous studies and how emotion affect word learning and the underlying neural mechanism have not been systematically investigated. 16 participants were trained to learn novel concrete or abstract words under negative, neutral and positive contextual emotions in continuous three days, and fufilled the testing tasks in day1 and day3 during fMRI scanning. We compared the brain activations in day1 and day3 aming to investigate the role of contextual emotions in learning different types of words and the corresponding neural plasticity changes. Behaviorally, the performance for the words learned in negative context was lower than the neutral and positive contexts, which indicated that the contextual emotions had significant impact on novel word learning. Correspondingly, the functional plasticity changes of the right angular (AG), bilateral insula and anterior cingulate gyrus (ACC) induced by word learning were modulated by the contextual emotions. And the insula also was sensitive to the concreteness of the learned words. More importantly, the functional plasticity changes of left inferior frontal gyrus(L IFG) and left fusiform(L FG) were interactively influenced by the contextual emotions and words’ concreteness, suggesting that the contextual emotional information had a discriminable effect on different types of words in the neural mechanism level. These results demonstrate that the emotional information in contexts is inevitable for word learning, and the role of contextual emotions in brain plasticity for learning was discussed.